2019
DOI: 10.17511/jooo.2019.i01.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pterygiumseverity on visual acuity and contrast sensitivity

Abstract: Aim: To evaluate prospectively the effect of pterygium excision on visual acuity and contrast sensitivity before and after surgery. Material & method: A prospective observational study where in 63 eyes of 63 patients with primary pterygia were studied before and after surgery. Examination was done in which contrast sensitivity was measured with pellirobson chart pre-operatively and one month postoperatively following pterygium excision with Conjunctival Limbal Auto Graft. Result: As the grade of pterygium incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…On the other hand, a few studies have researched evaluating the effect of pterygium excision in BCVA but with different morphologic features. Instead of pterygium's fleshiness, the grade was based on the extension of the apex of the pterygium of the cornea with four grades [ 16 , 17 ]. It was found that the BCVA improvement was statistically significant in grades II, III, and IV, in which the pterygium was described as crossing the limbus of the cornea between 2 mm and 4 mm or more than 4 mm and reaching up to the pupillary margin or had crossed the pupillary margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a few studies have researched evaluating the effect of pterygium excision in BCVA but with different morphologic features. Instead of pterygium's fleshiness, the grade was based on the extension of the apex of the pterygium of the cornea with four grades [ 16 , 17 ]. It was found that the BCVA improvement was statistically significant in grades II, III, and IV, in which the pterygium was described as crossing the limbus of the cornea between 2 mm and 4 mm or more than 4 mm and reaching up to the pupillary margin or had crossed the pupillary margin.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the BCVA improvement was statistically significant in grades II, III, and IV, in which the pterygium was described as crossing the limbus of the cornea between 2 mm and 4 mm or more than 4 mm and reaching up to the pupillary margin or had crossed the pupillary margin. Conversely, grade I, with the pterygium crossing the limbus by less than 2 mm from the cornea, was not significant with the improvement of BCVA ( p =0.184) [ 17 ]. According to Razmjoo et al [ 18 ], the reorganization of the surface of the tear film resulting from the mechanical effects induced by pterygium leads to the improvement of BCVA after excision surgery.…”
Section: Discussionmentioning
confidence: 99%